Analisa Simulasi Aliran Gas Buang pada Instalasi Exhaust Bengkel Las menggunakan Metode Computationl Fluid Dynamics-CFD dengan Flow Simulation-Solidwork - Riswan Eko Wahyu Susanto; Setyo Rojikin; M. Ainul Hakim (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Smoke hazards can result in poisoning of harmful gases produced by the welding process. So it is expected that in order to maintain air cleanliness in the welding workshop by installing an exhaust gas channel from welding, the purpose of this research is to analyse the flow of exhaust gas through simulation of fluid flow velocity (welding smoke) in the design of exhaust gas installation in the welding workshop using CFD or Computational Fluid Dynamics method. CFD simulation can predict in detail the movement of wind (moving fluid) in the welding fume exhaust duct. CFD simulation is carried out through three stages, namely pre-processing, solving, and post-processing. This CFD uses the Solidworks (Flow Simulation) application programme. It was found that the installation of a welding fume exhaust duct with an output capacity of 39 m³ per minute showed a significant increase in airflow velocity. The first simulation results at the exhaust fan (welding booth) showed a maximum velocity value of 13.14 m/s and an average velocity of 10.55 m/s, the Reynold's number was 84567.11. In the second simulation, with the axial fan (Fan stationary) at 2600 RPM and pipe diameter 127 mm, better results were obtained, namely minimum velocity of 12.88 m/s, average velocity 13.94 m/s, maximum velocity 14.53 m/s and Reynold's number 111512.74. So the simulation results show an improvement in the performance of the ventilation system, where the airflow velocity is quite good, which ensures the efficiency of the ventilation system.